Avances en sistemas de potencia y energía (2018)
Processing electrical energy is one of the most important research fields in our society. So far, tremendous efforts have been made to improve the efficiency of each step in electrical systems: generation systems have been enhanced by introducing renewable energy sources and new control systems for conventional generators, losses have been reduced, the power quality of distribution and transmission systems has been increased, the life-time and state-of-health of energy storage devices have been extended, and sections of the power grid have been isolated for intelligent energy management.